Revival: The Women Bonapartes vol. I (1908) - Williams, Hugh Noel, author.
1 online resource (434 pages)
Keywords: It will therefore, I think be admitted that the present volumes, in which I have endeavoured to give a full and unprejudiced history of the Women Bonapartes, call for no apology; and I may even venture to believe that, whatever their shortcomings, they will be welcomed by the English and American public as an attempt to fill a place in our Napoleonic literature which has been long vacant.